Adaptive evolution of chestnut forests to the impact of ink disease in Spain. Issue 4 (12th December 2019) - Alcaide, Francisco; Solla, Alejandro; Cherubini, Marcello; Mattioni, Claudia; Cuenca, Beatriz; Camisón, Álvaro; Martín, M. Ángela
Abstract: Phytophthora cinnamomi ( Pc ) is an extremely destructive soil‐borne pathogen of Asiatic origin responsible for "ink disease" in chestnut. This work assesses the adaptive potential to the impact of Pc of four Spanish populations of Castanea sativa undergoing different selection pressures. To explore the evolvability of C. sativa to Pc in the selected populations, parameters obtained from neutral and functional genetic diversity were compared with estimates of quantitative genetic variability. Nine expressed sequence tags‐simple sequence repeat (EST‐SSR) markers were selected and their transferability and polymorphism in 137 C. sativa individuals were evaluated. To test the potential of EST‐SSR markers for early selection of Pc tolerant plant material, the offspring of selected individuals were challenged with Pc . Expressed sequence tags‐simple sequence repeat markers and seedling life expectancy after Pc inoculation revealed significant different responses of C. sativa populations to Pc . The genetic variability observed within populations showed the potential response capacity of Spanish C. sativa populations to undergo fast adaptive evolution. The heritability value obtained for the "life expectancy" variable ( h 2  = 0.21 ± 0.11) indicated that selection for resistance to Pc is possible. Genetic patterns reflected two evolutionarily meaningful groupings of populations, corresponding to the different selective pressure of the oomycete between sites. The differentiation coefficient obtained through markers classified as under neutral selection ( F ST  = 0.185) was lower than the quantitative genetic differentiation of "life expectancy" between C. sativa populations ( Q ST  = 0.682), providing evidence that selection acted spatially in a heterogeneous manner. A first link has been identified in trees between population structure and adaptive responses to pathogen‐induced selection. The study identified one marker under positive selection that could be used in marker assisted selection to predict resistance to Pc in non‐inoculated C. sativa trees.